ANALYSIS OF THE VALUE OF RELIGIOUS MODERATION IN LEARNING MODULE OF ISLAMIC RELIGIOUS EDUCATION AND CHARACTER - Fauzi Muharom (Universitas Muhammadiyah Surakarta, 2023)
The study aims to analyze the value of religious moderation in module learning Islamic Religious Education and Character